2017
DOI: 10.1111/coa.12805
|View full text |Cite
|
Sign up to set email alerts
|

Temperament and character traits in patients with tinnitus: a prospective case series with comparisons

Abstract: There may be a connection between tinnitus and personality traits, especially in the case of 'novelty seeking', which is relatively constant over a lifetime. The TCI questionnaire may be useful in facilitating the application of personality traits to tailored counselling for tinnitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
1
0
1
Order By: Relevance
“…Welch and Dawes (2008) stated alongside Durai et al (2017) that compared to non-tinnitus control groups, tinnitus patients were more socially withdrawn, reactive to stress, and alienated as well as less self-controlled. Compared to an adult reference population, Chung et al (2017) reported that tinnitus patients showed higher levels of harm avoidance and lower scores for novelty seeking, reward dependence, persistence, cooperativeness and selftranscendence. Overall, studies demonstrated mixed relations between tinnitus-related distress and a variety of personality factors.…”
Section: Introductionmentioning
confidence: 84%
“…Welch and Dawes (2008) stated alongside Durai et al (2017) that compared to non-tinnitus control groups, tinnitus patients were more socially withdrawn, reactive to stress, and alienated as well as less self-controlled. Compared to an adult reference population, Chung et al (2017) reported that tinnitus patients showed higher levels of harm avoidance and lower scores for novelty seeking, reward dependence, persistence, cooperativeness and selftranscendence. Overall, studies demonstrated mixed relations between tinnitus-related distress and a variety of personality factors.…”
Section: Introductionmentioning
confidence: 84%
“…Modele te w większości za korelat tinnitusu zgodnie wskazują podwyższoną spontaniczną aktywność komórek nerwowych i/lub prawdopodobnie powiązaną z nią synchroniczność neuronalną. Część 4 to przegląd wybranych opracowań uwzględniających zaangażowanie procesów poznawczych i psychologicznych doprowadzających do (brzmiące jak pojedynczy ciągły ton, pisk) występują równo często lub nawet częściej (Turner, 1990;Pantev, Okamoto, Teismann, 2012;Hauptmann i in., 2015;Stein i in., 2016;Chung, Byun, Lee, Park, Jang, 2017). Termin "tinnitus" będzie stosowany zamiennie z jego polskim odpowiednikiem.…”
unclassified